Selective Regional Alteration of the Gut Microbiota by Diet and Antibiotics - Poteres, Elesa; Hubert, Nathaniel; Poludasu, Sudeep; Brigando, Gabriella; Moore, Julia; Keeler, Kelly; Isabelli, Allison; Ibay, Iara Cassandra V.; Alt, Lauren; Pytynia, Matthew; Ciancio, Mae; Martinez-Guryn, Kristina (Frontiers in Physiology, 2020)
The small intestinal gut microbiota has recently been implicated in contributing to metabolic disease. We previously demonstrated that diets rich in saturated milk fat have a particularly strong impact on the small bowel microbiota as opposed to more distal gastrointestinal (GI) regions. However, the impact of antibiotics and diet on the small bowel microbiota has not been clearly demonstrated. Thus, we sought to determine how diet and antibiotics interact in modulating the regional landscape of the gut microbiota. We conducted a study using male mice on a high fat (HF) or a low fat (LF) diet (n = 15/group) that received either water control (n = 5/diet), rifaximin, (non-absorbable broad-spectrum antibiotic; n = 5/diet) or an antibiotic cocktail consisting of metronidazole, cefoperazone, vancomycin, and neomycin (Abx cocktail; n = 5/diet). 16S rRNA sequencing was performed on mucosal scrapings collected from the small intestine and cecum, as well as on stool samples. Interestingly, antibiotics had a significant effect on community composition throughout the small intestine, cecum and stool, whereas diet significantly affected only the jejunum and cecum microbiota. The antibiotic cocktail, regardless of diet, was most effective in increasing cecum size, reducing body fat percentage, and plasma lipid levels. Altogether, this study reveals a selective and divergent regional alteration of the gut microbiota by diet and antibiotics.